Sick of Your Poor Neighborhood? Quasi-Experimental Evidence on Neighborhood Effects on Health - Linea Hasager; Mia Jørgensen (Institute of Labor Economics (IZA), 2024)
Does living in a low-income neighborhood have negative health consequences? We document causal neighborhood effects on health by exploiting a Spatial Dispersal Policy that quasi-randomly resettled refugees across neighborhoods from 1986 to 1998. Refugees allocated to low-income neighborhoods had a 12 percent higher risk of having developed a lifestyle related disease 8 to 15 years after immigration compared with those allocated to high-income neighborhoods. Our results suggest that interaction with neighbors and the characteristics of the immediate environment are important determinants for health outcomes. Differences in health care access, ethnic networks, and individual labor market outcomes cannot explain our findings.
Keywords: J15; I12; I14; I31; 330; health inequality; Refugee Dispersal Policy; lifestyle related diseases; neighborhood effects